Evaluation of a Telerehabilitation System for Community-Based Rehabilitation - Jamie L Schutte; Sara Gales; Ashlee Filipponi; Andi Saptono; Parmanto Bambang; Michael McCue (International Journal of Telerehabilitation)
The use of web-based portals, while increasing in popularity in the fields of medicine and research, are rarely reported on in community-based rehabilitation programs.  A program within the Pennsylvania Office of Vocational Rehabilitation’s Hiram G. Andrews Center, the Cognitive Skills Enhancement Program (CSEP), sought to enhance organization of program and participant information and communication between part- and full-time employees, supervisors and consultants. A telerehab system was developed consisting of (1) a web-based portal to support a variety of clinical activities and (2) the Versatile Integrated System for Telerehabilitation (VISyTER) video-conferencing system to support the collaboration and delivery of rehabilitation services remotely.  This descriptive evaluation examines the usability of the telerehab system incorporating both the portal and VISyTER. Telerehab system users include CSEP staff members from three geographical locations and employed by two institutions. The IBM After-Scenario Questionnaire (ASQ) and Post-Study System Usability Questionnaire (PSSUQ), the Telehealth Usability Questionnaire (TUQ), and two demographic surveys were administered to gather both objective and subjective information. Results showed generally high levels of usability.  Users commented that the telerehabilitation system improved communication, increased access to information, improved speed of completing tasks, and had an appealing interface. Areas where users would like to see improvements, including ease of accessing/editing documents and searching for information, are discussed.